Corticosteroids for bacterial corneal ulcers. Issue 2 (1st October 2008) - Srinivasan, M; Lalitha, P; Mahalakshmi, R; Prajna, N V; Mascarenhas, J; Chidambaram, J D; Lee, S; Hong, K C; Zegans, M; Glidden, D V; McLeod, S; Whitcher, J P; et al.
Abstract : Aims: The aim of the study was to conduct a preliminary clinical trial to assess whether adjunctive topical corticosteroids improve outcomes in bacterial keratitis and, if no difference was found, to determine the feasibility and sample size necessary for conducting a larger trial to answer this question. Methods: In this single centre, double-masked clinical trial, 42 patients with culture-confirmed bacterial keratitis at Aravind Eye Hospital in India were randomised to receive either topical prednisolone phosphate or placebo. All patients received topical moxifloxacin. The primary outcome was best spectacle-corrected visual acuity (BSCVA) at 3 months, adjusting for enrolment BSCVA and arm. Other pre-specified outcomes included re-epithelialisation time, infiltrate/scar size and adverse events. Results: Compared with placebo, patients in the steroid group re-epithelialised more slowly (hazard ratio 0.47, 95% CI 0.23 to 0.94). There was no significant difference in BSCVA or infiltrate/scar size at 3 weeks or 3 months. To have 80% power to detect a two-line difference in acuity, 360 cases would be required. Conclusions: Although corticosteroid treatment resulted in a statistically significant delay in re-epithelialisation, this did not translate to a significant difference in visual acuity, infiltrate/scar size or adverse events. To assess the effect of steroids on acuity, a larger trial is warranted and feasible. Trial registration number: NCT00324168